Analysis of Combustion Temperature in the Chopped Wood Gasification Process with Air Velocity Variation - Wijianto, W; Subroto, S; Sarjito, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
The general definition of gasification is thermo-chemical process of solid fuel form which becomes gas fuel with limited supply of O2 and it produces CH4, H2, CO, and impurity compound such as H2S, CO2, and tar. The objective of this research was to determine the influence of air velocity toward combustion temperature in order to invent the best values of air velocity for chopped wood gasification process.The research was commenced by preparing chopped wood as material for downdrft gasififier. Subsequently, glasswool was utilized as gasifier isolator in the gasification process to isolate heat in order to obtain the best heat efficiency. In the gasification processes, variaton of air speed was applied. The sample was chopped wood with gasification furnace in which the results of combustion temperature and combustion time were analyzed.The result indicated that the highest temperature was not depends on the fastest air flow velocity. Instead, it required a precise air flow velocity to gain the highest temperature. It was evidenced that the highest temperature gained was at 6200 C with v = 5.6 m/s air flow velocity. The longest gasification process was 13 minutes at v = 7.6 m/s and the fastestgasification process was 11 minutes at v = 5.6 m/s.